Non‐invasive micro Raman, SERS and visible reflectance analyses of coloring materials in ancient Moroccan Islamic manuscripts. (7th September 2012) - El Bakkali, A.; Lamhasni, T.; Haddad, M.; Ait Lyazidi, S.; Sanchez‐Cortes, S.; del, E.
<x xml:space="preserve">Abstract</x> For the first time, a thorough study of a variety of ancient Islamic manuscripts of Morocco was performed with the aim of identifying the coloring materials and recipes used by ancient scribes and illustrators in the western Mediterranean region. Six manuscripts collected from the old cities of Fez, Meknes and Zerhoune were chosen to cover a wide historical period and belonging to different scribal schools. They have been analyzed by Raman microscopy, surface enhanced Raman scattering and UV–visible diffuse reflectance measurements. The analyzed writings and illuminations include black, bright red, pink crimson, blue, green, dark brown and pale brown–orange inks. The identification of the observed wide range of the pigments leads to the statement that the coloring materials and recipes, used by ancient scribes and illuminators over centuries, remained the same in the western Mediterranean region. Copyright © 2012 John Wiley & Sons, Ltd.